GAMBARAN JAJANAN SEHAT DAN PERILAKU MEMILIH PANGAN JAJANAN ANAK SEKOLAH (PJAS) DI SD - Indah, Mawar Yanti; Bahar, Hartati; Hikmawati , Zainab (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to describe the behavior of choosing snacks, as well as knowledge, attitudes, perceptions, facilities, and peer support towards healthy snacks at SD Negeri 93 Kendari. This study uses quantitative methods and descriptive surveys, this study involved 54 out of 62 students selected through Stratified Random Sampling. The results showed that the majority of respondents had sufficient knowledge (81.48%), while a small portion was still lacking (18.52%). Most respondents showed a positive attitude (88.89%) compared to those who had a negative attitude (11.11%). A good perception of healthy snacks was found in (62.96%) respondents, while (37.04%) had a poor perception. As many as (85.19%) respondents considered the facilities and infrastructure adequate, while (14.81%) considered it inadequate. In addition, the majority of respondents (68.52%) received good peer support, while (31.48%) experienced inadequate support. This study shows that knowledge, attitudes, perceptions, facilities, and peer support. students about healthy snacks at SD Negeri 93 Kendari is quite good, but further efforts are needed to improve understanding of the importance of choosing safe and nutritious snacks for health. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan perilaku pemilihan jajanan, serta pengetahuan, sikap, persepsi, sarana, dan dukungan teman sebaya terhadap jajanan sehat di SD Negeri 93 Kendari. Penelitian ini menggunakan metode kuantitatif dan survei deskriptif, penelitian ini melibatkan 54 dari 62 siswa yang dipilih melalui Stratified Random Sampling. Hasil menunjukkan mayoritas responden memiliki pengetahuan cukup (81,48%), sementara sebagian kecil masih kurang (18,52%). Sebagian besar responden menunjukkan sikap positif (88,89%) dibandingkan dengan yang bersikap negatif (11,11%). Persepsi baik mengenai jajanan sehat ditemukan pada (62,96%) responden, sementara (37,04%) memiliki persepsi kurang. Sebanyak (85,19%) responden menilai sarana dan prasarana memadai, sedangkan (14,81%) menilai kurang memadai. Selain itu, mayoritas responden (68,52%) mendapatkan dukungan teman sebaya yang baik, sementara (31,48%) mengalami dukungan yang kurang. Penelitian ini menunjukkan bahwa pengetahuan, sikap, persepsi, sarana, dan dukungan teman sebaya. siswa mengenai jajanan sehat di SD Negeri 93 Kendari sudah cukup baik, namun diperlukan upaya lebih lanjut untuk meningkatkan pemahaman tentang pentingnya memilih jajanan yang aman dan bergizi untuk kesehatan.